Development of An Industry-Integrated Problem-Based Learning Model to Improve Work Readiness in The Field of Electric Vehicles for Vocational Students - Fanani Arief Ghozali; Bambang Sudarsono (JTP - Jurnal Teknologi Pendidikan, 2026)
Vocational High Schools (VHS) play a strategic role in preparing qualified and work-ready human resources to meet the demands of the energy transition era, particularly by equipping students with competencies in electric vehicle technology. However, the existing instructional practices remain predominantly teacher-centered and are insufficiently aligned with current industry needs. This study aims to develop and examine the effectiveness of a problem-based learning model integrated with industry (PL+ind) in enhancing vocational students’ work readiness in the electric vehicle sector. A research and development (R&D) approach was employed, encompassing preliminary study, needs analysis, expert validation, limited and extended field trials, and evaluation stages. Data were collected using observation sheets, interviews, questionnaires, and competency tests. The participants consisted of 15 vocational high schools and 12 industry partners, involving 88 teachers, 12 vice principals for curriculum, 220 students, and 35 automotive industry practitioners. Descriptive statistical analysis of expert validation results indicated that the PL+ind model achieved a high feasibility level, with a mean score of 3.40 on a four-point scale. The implementation results demonstrated a statistically meaningful improvement in students’ work readiness, as reflected in competency test scores that increased from a mean of 2.45 in the limited trial to 3.33 in the extended trial, both categorized as high achievement levels. The findings suggest that the PL+ind model effectively strengthens industry engagement in vocational learning processes and ensures alignment between school-based instruction and the evolving demands of the electric vehicle industry, thereby enhancing graduates’ work readiness.